Microphytoplankton composition in Barra das Jangadas estuarine system, (Jaboatão dos Guararapes, Pernambuco Statem, Brazil - Feitosa, Fernando Antônio do Nascimento; Cunha, Maria da Glória Gonçalves da Silva; Branco, Elisângela de Sousa (Arquivos de Ciências do Mar, 2017)
With the proposal to extend the studies about the ecology of the system of Barra das Jangadas, an important coastal system of the Pernambuco, this research was developed trying to determine the microphytoplanktonic composition, their seasonal and spatial distribution in different tides periods, frequency of occurrence, relative abundance, species diversity and equitability. The samples were collected monthly, from March, 1999 to February, 2000, through surface horizontal hauls, for three minutes, with a 65 micrometers mesh-size net. According to the results, could be observed that the most representatives groups were; Chrysophyta (76spp), Pyrrophyta (8spp), Euglenophyta (4spp), Cyanophyta (4spp) e Chlorophyta (4spp). About 66,7% of the species are distributed in the estuary, getting a high specific diversity in the deepest seasons that varied from 0,35 a 4,33 bits.cel-1, where 71,88% of the samples are understood between media and high diversity. Among the phytoplanktonics stand out: Bellerochea malleus (Brightwell) Van Heurk; Coscinodiscus centralis Ehrenberg; Oscillatoria sp; Pleurosigma sp; Cerataulus turgidas Ehrenberg; Euglena so; Thalassiosira sp, Nitzschia sigma (Kützing) Wm. Smith; Entomoneis alata (Ehrenberg) Kützing and Suriella fastuosa Ehrenberg with frequency higher then 70%. The diatoms quoted above are considerated eurihaline marines species and their presence in the studied environment is associated with a great volume os coastal Waters that normally get their way into Pernambuco State´s estuaries due to their small surface area.